2007
DOI: 10.1182/blood-2006-12-062448
|View full text |Cite
|
Sign up to set email alerts
|

CD34 facilitates the development of allergic asthma

Abstract: Asthma is a pulmonary inflammatory disease dependent on eosinophil and mast cell infiltration into the lung. CD34 is a sialomucin expressed by both of these cell types, and we have used CD34 Ϫ/Ϫ mice and a standard mouse model of asthma to evaluate the importance of CD34 expression on disease development. In comparison with wild-type (wt) mice, CD34 Ϫ/Ϫ mice exhibited a dramatic reduction in all hallmarks of allergic asthma, including lowered airway inflammatory cell infiltration, airway hyperresponsiveness, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 27 publications
3
99
0
Order By: Relevance
“…In our studies, we also found that Ship1 Ϫ/Ϫ -BMMC mice suffered worse allergic asthma pathology than Ship1 ϩ/ϩ -BMMC mice in an acute, OVA-induced (with alum adjuvant) model of allergic asthma (28). Because Kit W-sh/W-sh mice also developed symptoms of asthma, it made it difficult to determine to what extent Ship1 Ϫ/Ϫ mast cells were proinflammatory or whether they instead lacked the anti-inflammatory activity present in Ship1 ϩ/ϩ mast cells.…”
Section: Discussionmentioning
confidence: 50%
“…In our studies, we also found that Ship1 Ϫ/Ϫ -BMMC mice suffered worse allergic asthma pathology than Ship1 ϩ/ϩ -BMMC mice in an acute, OVA-induced (with alum adjuvant) model of allergic asthma (28). Because Kit W-sh/W-sh mice also developed symptoms of asthma, it made it difficult to determine to what extent Ship1 Ϫ/Ϫ mast cells were proinflammatory or whether they instead lacked the anti-inflammatory activity present in Ship1 ϩ/ϩ mast cells.…”
Section: Discussionmentioning
confidence: 50%
“…We have previously shown that CD34 and the related antigen CD43 are essential for the recruitment of MC precursors to peripheral tissues (24). More recent studies using inflammatory models suggest that loss of CD34 alone in many cases is sufficient to impede recruitment of MC precursors to peripheral tissues (8).…”
Section: Discussionmentioning
confidence: 99%
“…c-kit is a well known MC growth factor receptor, and mice bearing an inversion of the promoter (Kit Wsh/Wsh ) exhibit a selective defect in the ability to form mature MC. CD34 and CD43 are related cell surface sialomucins, and, although deletion of these genes has no effect on MCp formation in the BM, their loss leads to a profound impairment in the ability of MCp to traffic to peripheral tissues (8,24). To generate chimeras, APC ⌬468 mice were lethally irradiated and reconstituted with wt, Kit Wsh/Wsh or Cd34 Ϫ/Ϫ Cd43 Ϫ/Ϫ BM and analyzed 6 weeks later for polyps.…”
Section: Adenoma-associated Mastocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental murine lung inflammation was induced in mice previously colonized with murine or human feces, as previously described 17 with minor modifications. Although this model does not fully recapitulate the phenotype of human allergic asthma, it is a useful model for evaluating many aspects of this lung inflammatory disease.…”
Section: Experimental Lung Inflammation Modelmentioning
confidence: 99%